Factors Related to Tuberculosis Child: Literature Review - Asita Delyana Devi; Noor Alis Setiyadi (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
Background: Mycobacterium tuberculosis is a bacteria that causes pulmonary tuberculosis. TB disease can affect anyone, from adults to children. Purpose: To review the literature from various journals to explain the factors associated with the incidence of TB in children. The method used was literature review using three databases, namely Google Scholar, PubMed and Science Direct. The inclusion criteria used included the dependent variable was the incidence of child tuberculosis, the articles used were full text, ISSN journals indexed in Sinta and Scimago, and cross sectional research design. Meanwhile, the exclusion criteria used were articles that had been published for more than 10 years. Results: A total of 5 journals that have been analyzed explained that there was a significant relationship between nutritional status, close contact, and HIV status with the incidence of child tuberculosis. Conclusion: It is necessary to make efforts to eradicate tuberculosis in children, such as providing adequate nutrition and carrying out contact investigations in groups of close contact with adult TB patients.